PROGRAMAS EN CONTENIDOS CULTURALES EN EL MEDIO DE COMUNICACIÓN AUDIOVISUAL CALIDAD TV DEL CANTÓN EL EMPALME SECTOR 2 DE MAYO. AÑO 2022 - Cusme Mendoza, Skarlette Susana (2022)
The objective of this research is to examine the incidence of programs in cultural content in the quality TV audiovisual media of the canton El Empalme sector 2 de Mayo. The modality applied to this type of research is mixed, that is, qualitative and quantitative, since through the qualitative type we will be able to investigate, interpret and extract information through various sources through existing data such as the contributions of other studies carried out and in turn analyze the answers obtained through the survey and in terms of its quantitative type, we will be able to measure the rate of responses to the questions formulated in the survey to the inhabitants of the canton El Empalme sector 2 de Mayo. With the development of the information obtained, I was able to carry out through the analysis of my variables that the lack of cultural content does have a positive influence on those who are going to tune in. Although it is true that there were such programs in the audiovisual medium of TV quality, but over time it has had a decline in its entire audience and what I propose with my research topic is to be able to rescue culture through a digital magazine " Our Culture” clearly with the history, values and customs of the canton. The research technique that was used was the survey and the instrument led to a questionnaire made up of 7 open questions that was made to a group of 50 people to obtain answers through tabulations, and thus detect situations in the certain variants.